2019
DOI: 10.1140/epja/i2019-12780-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding astrophysical effects of nuclear symmetry energy

Abstract: Determining the Equation of State (EOS) of dense neutron-rich nuclear matter is a shared goal of both nuclear physics and astrophysics. Except possible phase transitions, the density dependence of nuclear symmetry Esym(ρ) is the most uncertain part of the EOS of neutron-rich nucleonic matter especially at supra-saturation densities. Much progresses have been made in recent years in predicting the symmetry energy and understanding why it is still very uncertain using various microscopic nuclear many-body theori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
168
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(178 citation statements)
references
References 619 publications
(1,186 reference statements)
10
168
0
Order By: Relevance
“…Its strong gravity may constraint or modify the equation of general relativity (GR) (Psaltis 2008;. To explore the observables of the NS is quite tricky due to its uncertainty in the equation of state (EoS) at supra saturation density, mainly the symmetry energy (Tsang et al 2009;Xu et al 2010;Horowitz et al 2014;Danielewicz & Lee 2014;Baldo & Burgio 2016;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Its strong gravity may constraint or modify the equation of general relativity (GR) (Psaltis 2008;. To explore the observables of the NS is quite tricky due to its uncertainty in the equation of state (EoS) at supra saturation density, mainly the symmetry energy (Tsang et al 2009;Xu et al 2010;Horowitz et al 2014;Danielewicz & Lee 2014;Baldo & Burgio 2016;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even though significant progress in constraining EOS of NSs from maximum masses and radii that extracted from NS property observations have been made up to now, the EOS of NSs, especially in the inner core is still unknown properly (please see Refs. [16,17] for a recent review and the references therein.). It is also reported that the gravitation wave (GW) signal emitted by compact binary objects will take a vital role in the future for understanding NSs properties [18].…”
Section: Introductionmentioning
confidence: 99%
“…n 0 refers to the saturation densities. In nuclear density functional theories, it was found that the slope of symmetry energy at saturation density has strong linear correlations with the neutron skins of 208 Pb and the symmetry energy [10,11]. In Fig.…”
Section: The Relativistic Brueckner-hartree-fock Model In Nu-cleamentioning
confidence: 91%